2020
DOI: 10.1039/d0an01232g
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal microfluidic lab-on-a-chip system with automated sample lysis, DNA amplification and microarray hybridization for identification of enterohemorrhagic Escherichia coli culture isolates

Abstract: The development of technology for the rapid, automated identification of bacterial culture isolates can help regulatory agencies to shorten response times in food safety surveillance, compliance, and enforcement as well...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…Automated RT-LAMP molecular diagnostic assay was implemented on a cartridge operated by the centrifugal microfluidic platform which is described in detail elsewhere. [40][41][42][43] The platform is equipped with a programmable pumping and pressure control system that can apply regulated air pressure to two microfluidic cartridges located on opposite ends of the rotating stage. A movable pneumatic manifold lid is used to interface each cartridge and apply pressure (between −5 and +10 psi) from the pump to dedicated pressure inlet ports within the microfluidic circuit.…”
Section: Centrifugal Microfluidic Platform and Cartridgementioning
confidence: 99%
See 1 more Smart Citation
“…Automated RT-LAMP molecular diagnostic assay was implemented on a cartridge operated by the centrifugal microfluidic platform which is described in detail elsewhere. [40][41][42][43] The platform is equipped with a programmable pumping and pressure control system that can apply regulated air pressure to two microfluidic cartridges located on opposite ends of the rotating stage. A movable pneumatic manifold lid is used to interface each cartridge and apply pressure (between −5 and +10 psi) from the pump to dedicated pressure inlet ports within the microfluidic circuit.…”
Section: Centrifugal Microfluidic Platform and Cartridgementioning
confidence: 99%
“…The platform is equipped with a programmable pumping and pressure control system to mediate fluid displacements on the cartridge. [40][41][42][43] The platform also features a stroboscopic imaging system for real-time visualization and recording of colorimetric signal, and thermoelectric elements integrated on the rotating stage for programmable, on-chip heating and cooling. The entire analytical workflow is conducted through a timed sequence of centrifugation and pneumatic actuation steps, which involve different operations such as downstream transfer, flow splitting, metering, inward pumping, and bubble-based mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Geissler et al . established a microfluidic device for performing the whole process of bacteria identification for E. coli O157:H7 from cell lysis, multiplex PCR amplification, to on-chip hybridization with fluorescent gene markers [ 198 ]. More recently, Sullivan et al .…”
Section: Microfluidic Devices and Biosensors For Sars-cov-2 Diagnosticsmentioning
confidence: 99%
“… 23 , 25 These characteristics render Zeonor and other COP formulations attractive for fabricating polymer-based microfluidic systems for analytical, diagnostic, and life science applications. 23 , 26 29 We previously have shown that periodic arrays of micropillars produced in Zeonor can be used as templates for colorimetric DNA detection. 30 The approach takes advantage of higher surface-to-volume ratios that these arrays provide compared to planar substrates, making it possible to attach more probe molecules per surface area and so increase the signal obtained by the assay.…”
Section: Introductionmentioning
confidence: 99%